Supramolecular Regulation of Polydopamine Formation by Amyloid Fibers. Issue 24 (15th April 2020) - Shin, J. H.; Le, Nghia T. K.; Jang, Hongje; Lee, Taehoon; Kang, Kyungtae
Abstract: Polydopamine (PD) and melanin species are chemically complex systems, the formation and properties of which are incompletely understood. Inspired by the role of functional amyloids in melanin biosynthesis, this paper examines the influences of the supramolecular structure of amyloids on oxidative polymerization of dopamine. Kinetic analyses on the formation of PD species in the presence of hen egg white lysozyme (HEWL) fibers or soluble HEWL revealed that both forms gave rise to the total quantity of PD species, but the rate of their formation could be accelerated only by the amyloid form. PD species formed with HEWL fibers showed a morphology of bundled fibers, whereas those with soluble HEWL had a mesh‐like structure. Amyloid fibers of recombinant Pmel17 had properties similar to those of HEWL fibers in modulating PD formation. The results presented here suggest how nature designs functionality with an amyloid structure and can help understand and engineer chemistries of other functional amyloids. Abstract : Roped together : Inspired by melanin biosynthesis process, amyloid fibers were used to regulate polydopamine formation. The presence of amyloid fibers accelerated polydopamine formation, and the resultant polydopamine–amyloid composites exhibited different materials properties to those of polydopamine. Amyloids made of different proteins had similar influences on polydopamine formation, indicating that the supramolecular structure is responsible for the observed regulating functions (see scheme).